Dermatoscopic signs in cutaneous leishmaniasis - María Librada Porriño Bustamante; Josefa Sánchez López; Carmen Dulanto Campos; Ramón Naranjo Sintes; María Antonia Fernández Pugnaire (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Dermoscopy is a non-invasive technique widely used to aid in the characterization and diagnosis of pigmented skin lesions. Recently, it has also been employed for the evaluation of non-pigmented skin tumours, and inflammatory and infectious cutaneous diseases. Although the diagnosis of cutaneous leishmaniasis is confirmed by the demonstration of amastigotes in infected skin or by the growth of promastigotes in culture medium, dermoscopy could be useful as a further diagnostic test. We report a patient with a nodular lesion located on the right cheek for almost two years. The lesion was clinically suggestive of cutaneous leishmaniasis. Dermoscopy showed yellow tears, erythema and vascular structures. The diagnosis was confirmed by the demonstration of amastigotes in a skin scraping sample.